Prospecting salivary tau as a diagnostic for Alzheimer’s type dementia - Gustavo Alves Andrade dos Santos; Francisco de Assis Carvalho do Vale; Valeria Paula Sassoli Fazan (Dementia & Neuropsychologia)
ABSTRACT Although recognized as one of the most critical and prevalent dementias, Alzheimer’s disease (AD) still does not have an affirmative biological marker, being diagnosed by excluding other pathologies that present similar symptoms. In the last decade, advances have been made in researching pathophysiological phenomena related to AD, with the identification of probable biomarkers. Some of these substances have a direct action on the degenerative activity that involves AD and may be associated with other pathological processes, such as inflammation and diabetes. Objective These occurrences led us to investigate further whether the levels of certain substances may be associated with the onset and progression of Alzheimer’s disease. Biomarkers can be found in plasma, saliva and cerebrospinal fluid. Methods This project investigated tau protein as a possible salivary biomarker in 76 patients, control group and Alzheimer’s, with different age groups, to establish a positive correlation between the studied biomarker and AD. Results Our findings showed that phosphorylated tau (pTAU) concentrations are higher in AD patients and somewhat lower in elderly patients without Alzheimer’s, but in young patients without Alzheimer’s the levels are much lower. Total tau had very similar levels in three groups evaluated. Conclusions Based on these results, we believe in the possibility of using saliva as an auxiliary method in diagnosing Alzheimer’s disease, with the advantages of low cost, non-invasiveness, and ease of collection. Still, more investigations will be needed to confirm this method presented.